Perspektif Humanistik Abraham Maslow untuk Menumbuhkan Karakter Siswa di Sekolah Menengah Atas - Aiman, Ghiyats; Arifi, Ahmad; Maryono, Maryono (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
There are many immoral acts that occur in the world of contemporary education, such as fighting, speaking harshly, being disrespectful to educators, cheating, Klitih and so on. This immoral act is the result of not achieving the full educational goals. A contextual approach is needed to achieve this goal, one of which is the approach of Abraham Maslow's humanistic theory. The method used is qualitative with the type of library research (literary research). Source of data in the form of documentation from books and journals. Data collection techniques using pick-up. The tactical steps in this study were to analyze by observing each data found from both relevant journals and books. The results of this study are that there are five hierarchical needs, namely physiological needs, security needs, needs for love and affection, needs for appreciation, and needs for self-actualization. The highest-level needs are self-actualization. It is in this need that all potentials are optimized and able to improve the cognitive abilities of high school students. Cognitive development is in line with affective development (attitude and character).